PHASE IDENTIFICATION OF SYNTHESIZED HYDROXYAPATITE IN DIFFERENT CALCINATION TEMPERATURE - Decky J. Indrani; Bambang Soegijono (Jurnal Sains Materi Indonesia, 2011)
PHASE IDENTIFICATION OF SYNTHESIZED HYDROXYAPATITE IN DIFFERENT CALCINATION TEMPERATURE. For bone tissue engineering, hydroxyapatite scaffolds for cell growth are attracting due to their bioactivity and similarity to human bone component. The sol-gel route used in previous studies provided high crystalline hydroxyapatite and second phase occurred at higher calcination temperature. The aim of the present research was to synthesize and characterize HA prepared using the wet precipitation method in different calcinations temperature. The synthesis of hydroxyapatite was prepared using calcium and phosphorous precursor. The synthesized hydroxyapatite were then calcined at temperatures up to 900 °C. Rietveld refinement was used to examine the entire XRD patterns and FT-IR measurement was employed to observe the functional group of the synthesized HA. Results showed that HA material with the apatite structure were produced as was analyzed by XRD and Rietveld refinements. Chemical analysis indicated the existence of P-O vibrational modes from phosphate group and O-H from absorbed water confirming the formation of HA. Rietveld analysis revealed the existance of CaO phase at 300 °C, however, it was not observed at higher calcination temperature. The present study indicated that the wet precipitation method has induced the formation of HA without CaO phase at temperature above 300 °C. HA with increased crystallinity were produced in line with the raise in temperature.